Androgen‐targeting therapeutics mitigate the adverse effect of GnRH agonist on the risk of neurodegenerative disease in men treated for prostate cancer. (16th March 2022) - Branigan, Gregory L.; Torrandell‐Haro, Georgina; Soto, Maira; Gelmann, Edward P.; Vitali, Francesca; Rodgers, Kathleen E.; Brinton, Roberta Diaz
Abstract: Background: Prostate cancer and multiple neurodegenerative diseases (NDD) share an age‐associated pattern of onset. Therapy of prostate cancer is known to impact cognitive function. The objective of this study was to determine the impact of multiple classes of androgen‐targeting therapeutics (ATT) on the risk of NDD. Methods: A retrospective cohort study of men aged 45 and older with prostate within the US‐based Mariner claims data set between January 1 and 27, 2021. A propensity score approach was used to minimize measured and unmeasured selection bias. Disease risk was determined using Kaplan–Meier survival analyses. Results: Of the 1, 798, 648 men with prostate cancer, 209, 722 met inclusion criteria. Mean (SD) follow‐up was 6.4 (1.8) years. In the propensity score‐matched population, exposure to ATT was associated with a minimal increase in NDD incidence (relative risk [RR], 1.07; 95% CI, 1.05–1.10; p  < 0.001). However, GnRH agonists alone were associated with significantly increased NDD risk (RR, 1.47; 95% CI, 1.30–1.66; p  <0.001). Abiraterone, commonly administered with GnRH agonists and low‐dose prednisone, was associated with a significantly decreased risk (RR, 0.77; 95% CI, 0.68–0.87; p  < 0.001) of any NDD. Conclusions: Among patients with prostate cancer, GnRH agonist exposure was associated with an increased NDD risk. Abiraterone acetate reduced the risks of Alzheimer's disease and Parkinson's disease conferred by GnRH agonists, whereas the risk for ALS was reduced by androgen receptor inhibitors. Outcomes of these analyses contribute to addressing controversies in the field and indicate that GnRH agonism may be a predictable instigator of risk for NDD with opportunities for risk mitigation in combination with another ATT. Abstract : Assessment of long‐term risk of developing neurodegenerative diseases in a clinical population of men with prostate cancer treated with androgen‐targeting therapeutics using medical bioinformatics tools. This figure was created with BioRender.com.